2010
DOI: 10.3402/ijch.v69i1.17386
|View full text |Cite
|
Sign up to set email alerts
|

Unintentional injuries among children and adolescents in Aboriginal and non-Aboriginal communities, newfoundland and labrador, Canada

Abstract: The rate of unintentional injury among children and adolescents in Aboriginal communities is higher than non-Aboriginal communities. Sex (male) and place of residence (Aboriginal communities) were strong predictors of unintentional injury in NL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
1
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 12 publications
2
38
1
3
Order By: Relevance
“…Of the 39 studies included in the review, 21 were from the USA,2 7 19 24 – 41 8 from Australia,4 8 42 – 47 7 from Canada3 5 48 – 52 and 3 from New Zealand 6 17 53. More than half the studies (n=23) presented mortality data,2 5 7 19 24 2628 30 31 3438 40 41 45 46 48 49 51 52 with the remainder investigating mortality and morbidity (n=8),3 6 8 39 42 47 53 54 morbidity only (n=7)4 17 29 33 43 44 50 and Years of Potential Life Lost (n=1) 25. All studies investigating morbidity outcomes were based on hospital data, the terms, morbidity and hospitalisation, are therefore used interchangeably hereafter.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 39 studies included in the review, 21 were from the USA,2 7 19 24 – 41 8 from Australia,4 8 42 – 47 7 from Canada3 5 48 – 52 and 3 from New Zealand 6 17 53. More than half the studies (n=23) presented mortality data,2 5 7 19 24 2628 30 31 3438 40 41 45 46 48 49 51 52 with the remainder investigating mortality and morbidity (n=8),3 6 8 39 42 47 53 54 morbidity only (n=7)4 17 29 33 43 44 50 and Years of Potential Life Lost (n=1) 25. All studies investigating morbidity outcomes were based on hospital data, the terms, morbidity and hospitalisation, are therefore used interchangeably hereafter.…”
Section: Resultsmentioning
confidence: 99%
“…Only five studies adjusted for covariates 26 30 39 41 44. Most studies derived an individual's indigenous status from a single source, mainly hospital morbidity or mortality data; however, five studies used an ecological study design where indigenous status was measured at an area level 3 49 – 52…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As injuries are one of the most common causes of morbidity and mortality in children and adolescents in North America, it is especially important to examine injury rates for this group in Aboriginal populations. Alaghehbandan, Sikdar, MacDonald, Collins, and Rossignol (2010) found that the hospital discharge rate of unintentional injuries, for each age category, was higher among Aboriginal children and youth populations in comparison to non-Aboriginal children and youth populations in Newfoundland and Labrador. Thus, while unintentional injuries are a concern in any population, they are of particular concern in Aboriginal populations.…”
Section: Injury Rates For Aboriginal Peoplesmentioning
confidence: 98%